Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine the value of [tex]\( x \)[/tex] for which [tex]\((f - g)(x) = 0\)[/tex], we start by defining the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ f(x) = 16x - 30 \][/tex]
[tex]\[ g(x) = 14x - 6 \][/tex]
Next, we need to find [tex]\((f - g)(x)\)[/tex], which is the difference between [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \][/tex]
Combine like terms:
[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \][/tex]
[tex]\[ (f - g)(x) = 2x - 24 \][/tex]
We are given that [tex]\((f - g)(x) = 0\)[/tex]. Therefore, we set the expression equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 24 = 0 \][/tex]
Add 24 to both sides of the equation:
[tex]\[ 2x = 24 \][/tex]
Divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{24}{2} \][/tex]
[tex]\[ x = 12 \][/tex]
Thus, the value of [tex]\( x \)[/tex] for which [tex]\((f - g)(x) = 0\)[/tex] is [tex]\( \boxed{12} \)[/tex].
[tex]\[ f(x) = 16x - 30 \][/tex]
[tex]\[ g(x) = 14x - 6 \][/tex]
Next, we need to find [tex]\((f - g)(x)\)[/tex], which is the difference between [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \][/tex]
Combine like terms:
[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \][/tex]
[tex]\[ (f - g)(x) = 2x - 24 \][/tex]
We are given that [tex]\((f - g)(x) = 0\)[/tex]. Therefore, we set the expression equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 24 = 0 \][/tex]
Add 24 to both sides of the equation:
[tex]\[ 2x = 24 \][/tex]
Divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{24}{2} \][/tex]
[tex]\[ x = 12 \][/tex]
Thus, the value of [tex]\( x \)[/tex] for which [tex]\((f - g)(x) = 0\)[/tex] is [tex]\( \boxed{12} \)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.